Volume 7: Industrial and Cogeneration; Manufacturing Materials and Metallurgy 2021
DOI: 10.1115/gt2021-59652
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Technologies for Fir Tree Slots: A Technological and Economic Evaluation

Abstract: Fir tree slots in engine disks pose a great challenge to the production process, especially due to the use of increasingly filigree geometries. Broaching with high-speed steel (HSS) as cutting tool material has been established as the state of the art process. However, this manufacturing process obtains the disadvantages of high tool costs and long waiting times in case of geometry adaptations. Alternative manufacturing technologies, namely electrochemical machining (ECM) and wire electrical discharge machinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…29 Vogtel et al put forward a broach structure of carbide inserts, optimized the shape of broach tooth for superalloy materials, and further improved the machining efficiency and ability for turbine disk slots. The experimental results showed that the processing efficiency of cemented carbide broaching tool was 4–10 times that of HSS broaching tool, the broaching force was reduced by nearly 35%, the thickness of the deformed layer of machined surface was reduced by about 50%, 30,31 as shown in Figure 6. Meanwhile, the wear law of surface coated and uncoated carbide broach inserts were preliminarily studied, which provided important experimental data reference for the popularization and application of high-speed broaching technology for turbine disk slots.…”
Section: Broachingmentioning
confidence: 95%
“…29 Vogtel et al put forward a broach structure of carbide inserts, optimized the shape of broach tooth for superalloy materials, and further improved the machining efficiency and ability for turbine disk slots. The experimental results showed that the processing efficiency of cemented carbide broaching tool was 4–10 times that of HSS broaching tool, the broaching force was reduced by nearly 35%, the thickness of the deformed layer of machined surface was reduced by about 50%, 30,31 as shown in Figure 6. Meanwhile, the wear law of surface coated and uncoated carbide broach inserts were preliminarily studied, which provided important experimental data reference for the popularization and application of high-speed broaching technology for turbine disk slots.…”
Section: Broachingmentioning
confidence: 95%